Protective Role of Trimetazidine Against Neomycin-induced Hair Cell Damage in Zebrafish - Chang, Jiwon (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2013)
OBJECTIVES: Trimetazidine (TMZ) is known to reduce the generation of oxygen-derived free radicals. The objective of the present study was to evaluate the effects of TMZ on neomycin-induced ototoxicity in transgenic zebrafish (Brn3C: EGFP). METHODS: Five-day, postfertilization zebrafish larvae were exposed to 125 µM neomycin and one of the following TMZ concentrations for 1 hour: 10 µM, 100 µM, 500 µM, 1,000 µM, 1,500 µM, or 2,000 µM. Hair cells within the neuromasts of the supraorbital (SO1 and SO2), otic (O1), and occipital (OC1) lateral lines were analyzed using fluorescence microscopy and confocal microscopy (n=10). Hair cell survival was calculated as a percentage of hair cells in the control group that were not exposed to neomycin. Ultrastructural changes were evaluated using scanning electron microscopy. RESULTS: TMZ protected against neomycin-induced hair cell loss in the neuromasts (TMZ 1,000 µM, 11.2±0.4 cells; 125 µM neomycin only, 4.2±0.5 cells; n=10; P<0.05) and decreased the terminal deoxynucleotidyl transferase (TdT)-mediated dUTP-biotin nick end labeling (TUNEL) reaction. In the ultrastructural analysis, structures of mitochondria and hair cells within the neuromasts were preserved in zebrafish exposed to 125 µM neomycin and 1,000 µM TMZ. CONCLUSION: TMZ attenuated neomycin-induced hair cell loss in zebrafish. The results of this study suggest that neomycin induces apoptosis, and that apoptotic cell death can be prevented by treatment with tremetazidine.